The method of research and structure analysis of the historic mortar. Part I – the macroscopic and microscopic - in visible light and electron microscopy - Klimek, Beata (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The former construction mortar differ significantly from the currently used. In many cases the historic mortar have very good physical-chemical properties. Therefore, the method of preparation of these mortars are still interesting for modern technology. But there is no precise guidance in archival technology. Therefore, attempting to re-create the old recipes make it sometimes very difficult. Set of methods in the study of historic mortars allow comparative analysis, as well as the reproduction of ancient recipes for modern conservation and technology of construction materials.